Eye health risks associated with unclean fuel: a meta-analysis and systematic review - Shi-Hang Chen; Yuan Tang; Song Xue; Song Xue (Frontiers in Public Health)
PurposeThis study comprehensively examined the correlation between unclean cooking fuels (UCF) and ocular health, covering diverse eye conditions such as cataracts, visual impairments, and ocular discomfort.MethodsAccording to MOOSE and PRISMA guidelines, a meta-analysis and systematic review was conducted on 28 studies from 3 databases. Literature quality was assessed using the Newcastle-Ottawa Scale. Heterogeneity among articles was gaged with the I2 statistic, sensitivity analysis used ‘leave-one-out test’, and publication bias was evaluated using Egger, Begg tests, and funnel plot analysis.ResultsThe study evidenced a significant association between UCF exposure and cataracts [OR 2.29, 95% CI (1.24, 4.23)], visual impairments [OR 1.70, 95% CI (1.45, 2.00)], and eye diseases/symptoms [OR 2.03, 95% CI (1.25, 3.29)]. However, no correlation was found between UCF exposure and glaucoma or elevated intraocular pressure [OR 0.96, 95% CI (0.84, 1.10), n = 2]. Subgroup analysis revealed that UCF cooking had an impact on nuclear cataracts [OR 1.98, 95% CI (1.67, 2.33), n = 4]. But not on cortical cataracts [OR 1.25, 95% CI (0.98, 1.60), n = 3]. Additionally, UCF exposure was linked to severe visual impairments like night blindness [OR 2.03, 95% CI (1.00, 4.96)], blindness [OR 1.43, 95% CI (1.32, 1.55)], and specific ocular symptoms such as tearing while cooking (OR = 3.20), eye irritation (OR = 2.58), and red eyes (OR = 2.03).ConclusionUCF cooking had significant impact on ocular health, notably on eye symptoms, cataracts, and visual impairments. UCF exposure presented demographic inequalities in cataract prevalence, while eye symptoms can serve as a reliable self-assessment of UCF exposure.